Caracterização físico-química de complexo de inclusão entre hidroximetilnitrofurazona e hidroxipropil-beta-ciclodextrina - Grillo, Renato [UNESP]; Melo, Nathalie F. S. de [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Brito, Charles L.; Trossini, Gustavo H. G.; Menezes, Carla M. S.; Ferreira, Elizabeth Igne; Moraes, Carolina Morales (Sociedade Brasileira de Química, 2008)
Hydroxymethylnitrofurazone (NFOH) is a prodrug that is active against Trypanosoma cruzi. It however presents low solubility and high toxicity. Hydroxypropyl-beta-cyclodextrin (HP-beta-CD) can be used as a drug-delivery system for NFOH modifying its physico-chemical properties. The aim of this work is to characterize the inclusion complex between NFOH and HP-beta-CD. The rate of NFOH release decreases after complexation and thermodynamic parameters from the solubility isotherm studies revealed that a stable complex is formed (deltaGº= 1.7 kJ/mol). This study focuses on the physico-chemical characterization of a drug-delivery formulation that comes out as a potentially new therapeutic option for Chagas disease treatment.
Physico-chemical characterization of inclusion complex between hydroxymethylnitrofurazone and hydroxypropyl-beta-cyclodextrin
Keywords: hydroxymethylnitrofurazone; cyclodextrin; inclusion complex